1998
DOI: 10.1093/humrep/13.10.2738
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood mononuclear cells stimulate progesterone production by luteal cells derived from pregnant and non-pregnant women: possible involvement of interleukin-4 and interleukin-10 in corpus luteum function and differentiation

Abstract: Human luteal cells have been reported to express human leukocyte antigen-DR and lymphocyte functional antigen-3 on the cell surface, suggesting physiological interaction between luteal cells and T-lymphocytes through the menstrual cycle into early pregnancy. To elucidate the role of peripheral lymphocytes on corpus luteum differentiation, the effect of peripheral blood mononuclear cells (PBMC) on steroidogenesis by luteal cells was investigated. The production of Th-2 cytokines such as interleukin (IL)-4 and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 43 publications
(44 reference statements)
2
63
0
2
Order By: Relevance
“…In this context, our results showing resistance of Cnr2 Ϫ/Ϫ females to LPSinduced preterm birth point toward an important concept that CB2 signaling is a contributing factor in regulating IL-10 levels and ovarian function after LPS challenge. Indeed, IL-10 was shown to stimulate P 4 production in human luteal cells in vitro (48). In contrast, there is also evidence that inflammation/infection induces proinflammatory cytokines, which causes ovarian luteolysis and drop in serum P 4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, our results showing resistance of Cnr2 Ϫ/Ϫ females to LPSinduced preterm birth point toward an important concept that CB2 signaling is a contributing factor in regulating IL-10 levels and ovarian function after LPS challenge. Indeed, IL-10 was shown to stimulate P 4 production in human luteal cells in vitro (48). In contrast, there is also evidence that inflammation/infection induces proinflammatory cytokines, which causes ovarian luteolysis and drop in serum P 4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Initial influx of neutrophils at ovulation is followed by a delayed monocyte chemotaxis, while a further selective increase in monocyte/macrophage number is observed at luteolysis (Brannstrom et al 1994). In addition, luteal macrophages display a pro-resolution M2-type phenotype characterised by phagocytic activity and Th2 cytokine production (Hashii et al 1998). Macrophages have been proposed as causal in the demise of the corpus luteum, being capable of producing many pro-apoptotic factors including TNF-a.…”
Section: Resolution Pathways In the Ovarymentioning
confidence: 99%
“…We found that PBMC derived from women in early pregnancy promoted progesterone production as much as that by HCG stimulation, suggesting that circulating blood immune cells in early pregnancy enhance CL function (Hashii et al, 1998). Based on these findings, we extended our hypothesis to the further concept that circulating immune cells transmit information about the presence of the developing embryo to various organs throughout the whole body and induce adequate functional change or differentiation in these organs to facilitate embryo implantation (Fujiwara, 2006).…”
Section: Immune Regulation Of Human CL Of Pregnancymentioning
confidence: 54%